A Collaborative Education Model Based on Religious Traditions through the Waladun Sholeh Activity at MA Progresif Ummul Quro - Lailatul farihah; Siti Aisyah; Indrawati; Slamet Efendi; Maulid Agustin (Al-Alim: Jurnal Pendidikan Agama Islam, 2026)
This study explores the implementation of a collaborative educational model grounded in religious traditions through the Waladun Sholeh program at MA Progresif Ummul Quro as a comprehensive strategy for character formation. Religious traditions including daily rituals, value habituation, teacher modeling, and school culture function as an integrated system that stabilizes moral behavior over time. Using a qualitative case study approach, the research examines the structure of collaborative interactions, coordination mechanisms, and the roles of teachers, students, and parents in the educational process. The findings reveal that structured collaboration fosters a consistent religious culture that effectively internalizes values such as discipline, responsibility, politeness, and spiritual awareness. The study concludes that religious traditions managed through collaborative frameworks can serve as a strong foundation for adaptive, relevant, and contextually grounded character education in modern Islamic schools.